Effect of cation distribution on the magnetic and hyperfine behaviour of nanocrystalline Co doped Ni–Zn ferrite (Ni0.4Zn0.4Co0.2Fe2O4). (April 2016) - Dalal, M.; Mallick, A.; Mahapatra, A.S.; Mitra, A.; Das, A.; Das, D.; Chakrabarti, P.K.
Graphical abstract: Highlights: Cation distribution in tetrahedral and octahedral sites of spinel Ni0.4 Zn0.4 Co0.2 Fe2 O4 . Structural analysis of observed X-ray diffraction pattern using Rietveld method. Study of hyperfine behaviour using Mössbauer spectroscopy. Static and dynamic magnetic measurements. Correlation of cation distributions obtained from Rietveld analysis with the results of magnetic and Mössbauer effect measurements. Abstract: Nanoparticles of Ni0.4 Zn0.4 Co0.2 Fe2 O4 are prepared by a simple co-precipitation method. The as dried sample is heat treated at 400, 500, 600, 700 and 800 °C to obtain different sizes of nanoparticles. The crystallographic phase of the samples is confirmed analyzing observed X-ray diffraction (XRD) by Rietveld method. Hyperfine parameters of the samples are derived from room temperature (RT) Mössbauer spectra of the samples. Magnetic properties of the samples are investigated by static and dynamic hysteresis loops. Different magneto-crystalline parameters are calculated from the variation of magnetization with temperature (M–T curve) under zero field cooled (ZFC) and field cooled (FC) conditions of the as dried sample. The cation distribution estimated from Rietveld analysis are correlated with the results of magnetic and Mössbauer effect measurements. The observed high value of saturation magnetization (72.7 emu/g at RT) of the sample annealed at 800 °C would be interesting for applications in different electromagnetic devices.